PENYULUHAN PENTINGNYA KESADARANDIRI DALAMBERLALULINTAS SESUAI ATURAN HUKUM YANG BERLAKU DI DUSUN DELES - Arif Fajar Wibisono (Asian Journal of Innovation and Entrepreneurship, 2014)
Dusun Deles, Jogonayan Village, District Ngablak, Magelang, Central JavaProvince that consisting of 3 RW and 12 RT. Mostly livelihood society is farmer.Beside farming, society also worked as traders, civil servants, worker etc. Thesociety in Dusun Deles are a society that havehigh desire to advance DusunDeles.Education progress in Dusun Deles is still below the average.Mostly, the education of the society were only maximum of Junior High School.Because of the low level education, the society awareness become less when itcomes to rule of law, especially about traffic rules. Many children under agealready driving a vehicle especially motorcycle. That case deemed to berevamped slowly but surely and because of that, author followed up thet casewith makes a program about the importance about self-awareness in trafficaccordance with the rule of law.